2017
DOI: 10.1080/14786419.2017.1380015
|View full text |Cite
|
Sign up to set email alerts
|

Phenoloxidase, an effective bioactivity target for botanical insecticide screening from green walnut husks

Abstract: Phenoloxidase, a critical enzyme in insects, may serve as a promising target in botanical insecticide development. In an effort to identify active ingredients with insecticidal properties in green walnut husks, juglone and plumbagin were isolated from the chloroform extract using phenoloxidase as bioactive target with the IC of 0.247 g/L and 0.256 g/L, respectively. After an artificial diet feeding of the juglone or plumbagin, more than 50% corrected mortality in stomach toxicity form was observed in Pieris ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 13 publications
4
7
0
Order By: Relevance
“…Therefore, the difference in fluorescence intensity between 1,4-NTQ and plumbagin would have been caused by their different nematicidal activities on B. xylophilus at the low concentration. Several studies revealed that quinones stimulate the production of ROS in various organisms [9,10,11,12,13,14]. Our results from the two assays also showed that naphthoquinone could obviously affect the generation of ROS in B. xylophilus, and thus, it was speculated that the nematicidal activity on B. xylophilus was caused by the ROS produced by the naphthoquinone.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Therefore, the difference in fluorescence intensity between 1,4-NTQ and plumbagin would have been caused by their different nematicidal activities on B. xylophilus at the low concentration. Several studies revealed that quinones stimulate the production of ROS in various organisms [9,10,11,12,13,14]. Our results from the two assays also showed that naphthoquinone could obviously affect the generation of ROS in B. xylophilus, and thus, it was speculated that the nematicidal activity on B. xylophilus was caused by the ROS produced by the naphthoquinone.…”
Section: Discussionsupporting
confidence: 71%
“…Naphthoquinone is a class of organic compounds structurally related to naphthalene and is easily found in nature as products of microorganisms and as secondary metabolites in plants. The bioactivities, such as potential antibacterial, insecticidal, and nematicidal effects, have been studied [9,10,11,12,13,14]. The mechanism of naphthoquinone in organisms is related to enhanced reactive oxygen species (ROS) generation and results in the death of cells [15].…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that there might be a threshold of about 1 mg g −1 food before the S. littoralis larvae begin to die. The experiment is somehow comparable with a recent study by Hu and colleagues [42]. They investigated the mortality of Pieris rapae and Helicoverpa armigera feeding on cabbage leaves dipped into solutions with different concentrations of plumbagin and juglone, respectively.…”
Section: Growth-inhibiting and Larvicidal Activities Of Plumbaginsupporting
confidence: 77%
“…Besides the hypothesis that NQ are involved in defense against microbial infection, there are several studies showing that these compounds can also affect insects [31][32][33][38][39][40][41][42][43]. We, therefore, performed feeding experiments with plumbagin-supplemented artificial diet and measured the weight of S. littoralis larvae every day.…”
Section: Growth-inhibiting and Larvicidal Activities Of Plumbaginmentioning
confidence: 99%
“…Using metabolomics analysis, it was demonstrated that the juglone caused a disturbance of the Apis gossypii physiology by affecting its hemolymph metabolomic profile [335]. Finally, Hu et al [336] found that juglone inhibits phenoloxidase activity in haemolymph of larvae of Pieris rapae Linne and Helicoverpa armigera Hübner. In insects, phenoloxidase plays an important role in the developmental processes of immunity defence, and its inhibitor has a perspective as a bioinsecticide.…”
Section: Natural Biopesticides Originated From Treesmentioning
confidence: 99%